Challenges and accurate estimates of mortality and case-fatality rates due to COVID-19. (November 2020) - Azizi, H.; Esmaeili, E.D.; Fakhari, A.
Abstract: Many reasons restrict obtaining an accurate estimate of Case Fatality Rate (CFR) and Mortality Rate (MR) by COVID-19. The main concern is the number of infected people and deaths. We aimed to discuss some solutions for accurate estimating of CFR and MR.